Study of fly ash based geopolymer mortar : citric acid and sucrose as proposed natural based retarder - Mohd Sobri, Ibrahim (2012)
The geopolymer then has been introduced by Joseph Davidovits as a new binder to replace the OPC. The current limitation of geopolymer concrete, it only can be produce in precast concrete industries. Ibis case study is conducted to find a retarder that can slow the reaction of geopolymer so it can be transferred from mixture plant and can be cast in situ at site. Natural based retarders that proposed to use in this case study are sucrose and citric acid. The percentage ofretarder were used are 0%, 1.5% and 2.5%. Not only focusing on that matter, this case study also investigating about the strength of 50mm x 50mm x 50mm cube that has been exposed to different type curing condition, ambient and oven ( 60°). Compressive tests (ASTM Cl 09M) were conducted after I day, 7 day, 28 day and 56 day. Furthermore, flow table test (ASTM Cl437) also were conducted to measure the flow ability of fresh geopolymer mortar. After that, porosity test (ASTM C642) also were conducted to hardened geopolymer mortar to find out the percentage of porosity of the cube. Lastly, fresh geopolymer paste will undergo vicat test (ASTM C191) to measure the setting time of the paste. Total sample consist 140 hardened mortar and 5 fresh geopolyrner paste sample for vicat test. The result of compressive strength between 1.5% sucrose and control sample has shown no significant different, so the strength is as good as control sample. More retarder added to the geopolymer mortar, more it will affected the compressive strength. Increasing citric acid will only accelerate the reaction of geopolymer paste. On the other hand, increasing of sucrose will retarded and slow the reaction of geopolymer paste.